Auditory brainstem response testing using intranasal dexmedetomidine sedation in children: a pilot study. (1st July 2021) - Godbehere, Joanna; Harper, Samuel; Loxey, Teresa; Kirton, Christine; Verma, Rohit; Carr, Simon
Abstract: Objective: Auditory brainstem response (ABR) is used to determine hearing thresholds in children who cannot undergo behavioural testing. Children must remain still during testing, with general anaesthesia (GA) in theatre required for those who cannot. We developed a protocol whereby an ABR was undertaken in a ward environment using only intranasal dexmedetomidine for sedation. Design: Prospective data were collected including the time of sedation onset, ABR duration and arrival to discharge time was recorded and feedback was requested using a questionnaire. Study sample: Twenty-nine consecutive patients routinely undergoing an ABR. Results: From this pilot study, we demonstrated that intranasal dexmedetomidine could be used successfully to administer safe sedation to all twenty-nine children undergoing an ABR in a ward environment as opposed to theatre. Conclusions: This allowed for faster time to discharge compared to GA, produced what was felt to be a better quality ABR trace, better utilization of a theatre slot, negated the need for GA in a child and created a less stressful experience for both parent and child according to information from feedback questionnaires.